Insecticidal Activity of Grape Pomaces from Two Grape Cultivars Against the Housefly (Musca Domestica L.) Under Laboratory Conditions - Abdul-Lateef Molan; Mohamad Q. Balasim; Nagham Y. Al-Bayati (Tropical Life Sciences Research, 2018)
Aqueous extracts prepared from the powdered entire pomaces and their parts (seeds and peels) of two Iraqi grape cultivars (Shada and Des-Alanez) were evaluated for their ovicidal, larvicidal, and pupicidal activities against housefly, Musca domestica (Linnaeus 1758) and compared them with chemical insecticide (Agita 10 WG; Austria). The highest insecticidal activity was shown by the aqueous extracts of powdered seeds followed by the entire pomace and then peels. The water extracts from the seeds, peels and pomaces were able to inhibit completely the hatching of the eggs at a concentration of 150 ?g/ml while the Agita insecticide was able to inhibit the hatching process at a concentration of 50 ?g/ml. The water extracts also were able to kill the L3 larvae and the activity was increasing with the increasing of the concentration. It is very interesting to note that the addition of the powdered entire pomaces, seeds, and peels on top or at the bottom of the cow manure was able to inhibit the development of up to 50% and 47.5% of L1 to pupae and to adult flies, respectively. Taking into consideration the huge amounts of grape pomaces that produced annually, the cheap price and the ease in dealing with, make them a good candidate as alternative insecticides and environmentally more friendly than the chemical insecticides.